Effects of dietary vitamin K3 supplementation on vitamin K1 and K2 (menaquinone) dynamics in dairy cows. (13th January 2022) - Bai, Hanako; Arai, Hikoji; Ikuta, Kentarou; Ishikawa, Sho; Ohtani, Yoshihisa; Iwashita, Kunihiro; Okada, Nao; Shirakawa, Hitoshi; Komai, Michio; Terada, Fuminori; Obara, Yoshiaki
Abstract: The effect of dietary vitamin K3 (VK3) on ruminant animals is not fully investigated. The aim of this study was to examine the effects of dietary VK3 on lactation performance, rumen characteristics, and VK1 and menaquinone (MK, or VK2) dynamics in the rumen, plasma, and milk of dairy cows. Eight Holstein dairy cows in late lactation periods were used in two crossover trials including a control (nontreatment) and a 50 or 200 mg/day (d) VK3 supplementation group. After 14 days, plasma, ruminal fluid, and milk were sampled and their VK1 and MKs contents were measured using fluorescence‐high‐performance liquid chromatography (HPLC). Milk production was unchanged after feeding 50 mg/day VK3 but marginally decreased after feeding 200 mg/day VK3. The molar ratio of propionate in ruminal fluid was significantly increased on feeding 200 mg/day VK3. Additionally, MK‐4 concentrations significantly increased in both plasma and milk after VK3 feeding (50 and 200 mg/day). In ruminal fluid, MK‐4 concentrations increased after 200 mg/day VK3 feeding. These results suggest that VK3 may be a good source of MK‐4, the biologically active form of VK, in Holstein dairy cows during their late lactation periods. This study provides a basis for understanding the physiological role of VK in dairy cows.